On-demand electrically controlled drug release from resorbable nanocomposite films. Issue 42 (23rd October 2017) - Samanta, Devleena; Mehrotra, Rohan; Margulis, Katy; Zare, Richard N.
Abstract : A resorbable nanofilm that dissolves with local pH changes induced by electrical stimuli has been developed for electroresponsive drug delivery. Abstract : Electroresponsive materials are promising carriers for developing drug delivery systems (DDSs) with excellent spatial, temporal, and dosage control over drug release. Current electroresponsive systems use high voltages (2–25 V), are not bioresorbable, or use materials with unknown long-term biocompatibility. We report here a nanocomposite film that is resorbable, electroresponsive at low voltages (<−2 V), and composed of entirely FDA-approved materials. Our DDS is based on poly(methyl methacrylate- co -methacrylic acid), commercially marketed as Eudragit S100 (EGT), which has pH-dependent aqueous solubility. Nanometric films of drug-loaded EGT were designed, synthesized, and coated with a protective layer of chitosan. We hypothesized that electric stimuli would cause local pH changes on the working electrode, leading to pH-responsive dissolution of EGT with concomitant drug release. Our results confirm that local pH changes impart electroresponsive release behavior to the films. Furthermore, drug release scales linearly with voltage, current, and time. The generalizability of the system is shown through the release of several molecules of varying hydrophobicity, p K a, and size, including fluorescein (free acid and sodium salt), curcumin, meloxicam, and glucagon. The ability to modulate drug release with the applied stimulus can be utilized to design minimally invasive drug delivery devices based on bioresorbable electronics. Such devices would allow for personalized medicine in the treatment of chronic diseases.